1995
DOI: 10.3354/meps117229
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-specific growth and loss rates for dominant phytoplankton populations from the northern Gulf of Mexico

Abstract: Taxon-specific growth and sedimentation rates of dommant phytoplankton were measured during 2 cruses (summer 1990 and spring 1991) in the northern Gulf of Mexico as part of the NOAA Nutrient-Enhanced Coastal Ocean Productivity (NECOP) program. Microzooplankton grazing rates also were measured during the summer cruise. During each of the cruises, a series of stations from the Mississippi River mouth to the hypoxia region (located ca 50 to 100 km west) were sampled to examme variability of growth and loss proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 42 publications
(46 reference statements)
5
31
1
Order By: Relevance
“…Except at the far-field station, phytoplankton growth rates were all higher than 1 doubling per day, with the growth rate of the > 20 µm phytoplankton higher than 2 doublings per day at some stations. These rates are within the ranges of previous reports (Fahnenstiel et al 1995, Strom & Strom 1996 which also showed nutrient limitation of phytoplankton growth in the far-field or offshore sites, with diatoms the most severely affected.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Except at the far-field station, phytoplankton growth rates were all higher than 1 doubling per day, with the growth rate of the > 20 µm phytoplankton higher than 2 doublings per day at some stations. These rates are within the ranges of previous reports (Fahnenstiel et al 1995, Strom & Strom 1996 which also showed nutrient limitation of phytoplankton growth in the far-field or offshore sites, with diatoms the most severely affected.…”
Section: Discussionsupporting
confidence: 74%
“…Under far-field conditions slightly farther to the west, phytoplankton growth rates were nutrient-limited (Strom & Strom 1996) and the microzooplankton grazing to phytoplankton growth ratio was typically between 0.3 and 0.9. In contrast to Fahnenstiel et al (1995), Strom & Strom (1996) observed significant consumption of large diatoms by microzooplankton (heterotrophic dinoflagellates) at some stations. It appears that a large fraction of the river nitrate incorporated into nanophytoplankton, and a smaller fraction of nitrate incorporated into larger phytoplankton, are grazed by microzooplankton.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…These observed growth rates varied considerably between taxa with lowest values of <0.1 d −1 and maximum rates of 3 d −1 . Since our model considers only one phytoplankton group, which represents the whole phytoplankton community, we compare the simulated rates with the observed mean and median growth rates of Fahnenstiel et al (1995). In March 1991 the observed mean and median rates were 0.5 and 0.4 d −1 , respectively, and agree …”
Section: Phytoplankton Growth Ratesmentioning
confidence: 83%
“…The Mississippi River is the 7th largest freshwater input into the world's oceans (Milliman & Meade 1983), and strongly affects the biological productivity of the northern Gulf of Mexico shelf (Walsh 1988, Fahnenstiel et al 1995, Rabalais et al 2002. The region surrounding the Mississippi Delta is in fact so productive that it accounts for 70 to 80% of Gulf of Mexico (GOM) fishery landings (Lohrenz et al 1999, Grimes 2001, the US portion, of which alone was valued at ca.…”
Section: Introductionmentioning
confidence: 99%